Middle Cerebral Artery Occlusion with Moyamoya-Like Vessels and Aneurysms: A Report of Two Cases. Issue 1 (January 2014) - Rivera, Rodrigo; Sordo, Juan; Badilla, Lautaro; Bravo, Eduardo; Riveros, Rodrigo; Giacaman, Pablo
We describe two cases of aneurysmal rupture in moyamoya-like vessels in middle cerebral artery occlusion. This phenomenon was previously described in severe steno-occlusive disease and accounts for the hemorrhagic presentation. To our knowledge, these are the second and third clinical cases published in modern neuroradiological literature.